Teori Pendidikan Keluarga dan Tanggung Jawab Orang Tua dalam Pendidikan Anak Usia Dini - Lismayanti, Ima; Gunawan, Yusuf Agung; Budiarti, Lolita Singgih; Sukatin, Sukatin; Yusup, Muhammad (Medan Resource Center, 2022)
He talked about parents' responsibilities in early childhood education. It is known from the literature that the home environment plays an important role in the upbringing of children. Father and mother in the family become the first educators in the developmental process of the child's life. Parents build relationships and not only create different families for reproductive purposes, but also continue the lineage and build affection. The main task of the family is to create the building and atmosphere of the family upbringing process, so that the next generation of intellectual and noble generations stands as a solid foundation for the life and journey of human children. can do. This fact is supported by theoretical insights showing the importance of home education as a child's first basic education.